Molecular polymorphisms of the nuclear and chloroplast genomes among African melon germplasms reveal abundant and unique genetic diversity, especially in Sudan - (:unkn) unknown (My University, 2025)
Background and Aims Africa is rich in wild species of Cucumis and is considered one of the places of origin of melon. However, our knowledge of African melon is limited, and genetic studies using melon germplasms with wide geographical coverage are required. Here, we analysed the genetic structure of African melons, with emphasis on Sudan. Methods Ninety-seven accessions of African melon were examined along with 77 reference accessions representing Asian melon and major horticultural groups. Molecular polymorphisms in the nuclear and chloroplast genomes were investigated using 12 RAPD, 7 SSR and 3 SNP markers. Horticultural traits, including seed size, were measured for 46 accessions, mainly from Sudan. Key Results African melons were divided into large and small seed-types based on seed length: large seed-type from Northern Africa and small seed-type from Western and Southern Africa. Both seed types are common in Sudan. Molecular genetic diversity in these geographical populations was as high as in India, the Asian centre of melon domestication. Large seed-types from Northern Africa were assigned to Pop4 by structure analysis and had Ib cytoplasm in common with Cantalupensis, Inodorus and Flexuosus. Small seed-types were highly diversified and geographically differentiated; specifically, Pop1 with Ia cytoplasm in Southern Africa and South Asia, Pop2 with Ia in East Asia, including Conomon and Makuwa, and Pop3 with Ia or Ic in Africa. Sudanese small seed-types were grouped in Pop3, while their cytoplasm type was a mixture of Ia and Ic. Sudanese Tibish had Ic cytoplasm, which was unique in Africa, common in Western Africa and Sudan, and also found in wild or feral types. Conclusions Melon of Ic lineage, including Tibish, originated from wild melon in the ‘western Sudan region’, and independently of melon with Ia or Ib cytoplasm, which originated in Asia. This clearly indicates the polyphyletic origin of melon.
Keywords: African Research